Treatment of complicated hypertension - Kuch-Wocial, Agnieszka; Maciejewska, Monika; Łoń, Izabela (Przewodnik Lekarza/Guide for GPs, 2007)
This paper presents European Experts’ opinion on hypertensive treatment of patients with established cardiovascular disease and cardiovascular disease equivalents such as diabetes. Treatment of coronary artery disease, heart failure, diabetes, non-diabetic nephropathy and stroke based on ESH and ESC 2007 guidelines is discussed.